2009
DOI: 10.1073/pnas.0811706106
|View full text |Cite
|
Sign up to set email alerts
|

An adrenal β-arrestin 1-mediated signaling pathway underlies angiotensin II-induced aldosterone production in vitro and in vivo

Abstract: Aldosterone produces a multitude of effects in vivo, including promotion of postmyocardial infarction adverse cardiac remodeling and heart failure progression. It is produced and secreted by the adrenocortical zona glomerulosa (AZG) cells after angiotensin II (AngII) activation of AngII type 1 receptors (AT1Rs). Until now, the general consensus for AngII signaling to aldosterone production has been that it proceeds via activation of Gq/11-proteins, to which the AT1R normally couples. Here, we describe a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
120
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 40 publications
5
120
0
Order By: Relevance
“…Of note, Lymperopoulos et al recently reported that aldosterone secretion through AT1R was mediated by ß-arrestin. 29 This was shown in vitro in the human adrenocortical zona glomerulosa cell line H295R and in vivo in normal rats with adrenal gland-specific overexpression of ß-arrestin1. Transfection of the H295R cells with a dominant negative ß-arrestin1 mutant significantly reduced angiotensin-induced aldosterone production.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, Lymperopoulos et al recently reported that aldosterone secretion through AT1R was mediated by ß-arrestin. 29 This was shown in vitro in the human adrenocortical zona glomerulosa cell line H295R and in vivo in normal rats with adrenal gland-specific overexpression of ß-arrestin1. Transfection of the H295R cells with a dominant negative ß-arrestin1 mutant significantly reduced angiotensin-induced aldosterone production.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we examined the impact of this on the physiological effect of AT1R-induced aldosterone production in vitro. Using the human AZG cell line H295R, transfected to overexpress arr1 [4] , and in vitro aldosterone secretion as the readout, we found that candesartan and valsartan are by far the most potent aldosterone secretion inhibitors in vitro ( Fig. 1) [11] .…”
Section: Research Highlightmentioning
confidence: 99%
“…1), which significantly exacerbates post-MI HF [4][5][6] . Of note, the prototypic drug of the ARB class losartan appears ineffective at blocking the adrenal arr1-dependent aldosterone production and hence, at suppressing circulating aldosterone post-MI [5] .…”
mentioning
confidence: 99%
“…Next, we examined the impact of this on the physiological effect of AT1R-induced aldosterone production in vitro. Using the human AZG cell line H295R, transfected to overexpress arr1 [4] , and in vitro aldosterone secretion as the readout, we found that candesartan and valsartan are by far the most potent aldosterone secretion inhibitors in vitro [11] . Olmesartan also displays some limited capability of suppressing secretion but losartan and irbesartan are…”
mentioning
confidence: 99%
“…AT1R is a G protein-coupled receptor (GPCR) that also signals through G protein-independent pathways, a plethora of which are mediated by the scaffolding actions of arrestins (arrs), originally discovered as terminators of GPCR signaling [3] . AngII elicits aldosterone synthesis and secretion via both G proteins and arrs (specifically arr1) [4][5][6] . Of note, the prototypic drug of the ARB class losartan appears ineffective at blocking the adrenal arr1-dependent aldosterone production and hence, at suppressing circulating aldosterone [5] .…”
mentioning
confidence: 99%